2015
DOI: 10.3389/fnhum.2015.00467
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Basal Ganglia and Right Frontoparietal Network in Early Drug-Naïve Parkinson’s Disease during Heat Pain Stimuli and Resting State

Abstract: Background:The symptoms and pathogenesis of Parkinson's disease (PD) are complicated and an accurate diagnosis of PD is difficult, particularly in early-stage. Because functional magnetic resonance imaging (fMRI) is non-invasive and is characterized by the integration of different brain areas in terms of functional connectivity (FC), fMRI has been widely used in PD research. Non-motor symptom (NMS) features are also frequently present in PD before the onset of classical motor symptoms with pain as the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…For example, dysfunction of somatomotor networks is not surprising, given the characteristic motor manifestations of PD (Jankovic 2008) and previous reports of their disruptions (Hacker et al 2012;Gottlich et al 2013;Olde Dubbelink et al 2014;Campbell et al 2015;Canu et al 2015;Gorges et al 2015;Tan et al 2015;Guimaraes et al 2016;Koshimori et al 2016;Peraza et al 2017). However, we show disruptions of internetwork somatomotor interactions.…”
Section: Pd Impacts Specific Cortical and Subcortical Network And Esupporting
confidence: 66%
“…For example, dysfunction of somatomotor networks is not surprising, given the characteristic motor manifestations of PD (Jankovic 2008) and previous reports of their disruptions (Hacker et al 2012;Gottlich et al 2013;Olde Dubbelink et al 2014;Campbell et al 2015;Canu et al 2015;Gorges et al 2015;Tan et al 2015;Guimaraes et al 2016;Koshimori et al 2016;Peraza et al 2017). However, we show disruptions of internetwork somatomotor interactions.…”
Section: Pd Impacts Specific Cortical and Subcortical Network And Esupporting
confidence: 66%
“…They found that functional network connectivity between the basal ganglia and salience network is reduced during both states in PD. In addition, the right frontoparietal network was significantly disturbed during evoked pain .…”
Section: Neuroimagingmentioning
confidence: 99%
“…the amygdala, ventral striatum and substantia nigra/ventral tegmental area [54]. Several studies have shown that chronic pain shifts salience network activity [54,55], whereas other studies have indicated that, in PD, activity of the salience network is affected by cognitive and motor dysfunction [56][57][58].…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The BGN is a group of subcortical nuclei involved in motor control, cognition and emotional processing . Thyrotoxicosis patients show symptoms such as impaired cognition, trembling, heat intolerance and emotional imbalance.…”
Section: Discussionmentioning
confidence: 99%